Identify Location Characteristics of Tourism Accommodation that are Influenced by e-Commerce Case Study: Lembang Tourism Area, Kab. West Bandung - Dewantara, Oky; Cungwin, Ardelia Jessica; Muhammad, Fadhil; Putri, Reliya Annisa; Cahyaningtyas, Mutia Ayu (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
The presence of the Industrial Revolution 4.0, which is marked by the rapid development of the internet, has fundamentally changed the way humans live, work, and communicate with each other. This development has also influenced the development of the business of providing accommodation in tourist areas. The ease of obtaining information via an internet network that is connected to regional areas opens up opportunities for the public to market tourist accommodation through e-commerce accommodation. The Lembang tourist area is an area with high potential for the development of e-commerce accommodation, covering 25.64% of tourist attractions in West Bandung Regency. This research aims to determine trends and developments in the characteristics of business locations providing accommodation in the Lembang tourist area based on observations via digital platforms. Data was obtained using a spatial analysis method with two different functions. The classification function is used to review location characteristics in businesses providing accommodation based on road class. The neighborhood function is used to review location characteristics based on proximity to tourist centers. The data was then analyzed descriptively and qualitatively. The results of the research show that the development trend of e-commerce accommodation in accommodation provision businesses continues to grow from year to year. Observation results via digital platforms show that as many as 136 accommodation business units were incorporated into e-commerce accommodation in 2019 in the Lembang tourist area. The location characteristics of the business providing accommodation tend to be concentrated around tourist areas with a radius of 1 km from the tourist center. Judging from the characteristics of business locations providing accommodation on roads, it is known that 59% of business units are predominantly located on neighborhood roads, while 41% are on main roads. The ease of access offered by this digital platform influences the development of business providing accommodation and location on the road class but does not significantly affect the distance to tourist centers.